Indissoluble marriage and patriarchal family, pillars of anti-communist struggle. The crusade perspective and its transition to "Tradition, Family and Property" in the sixties - Scirica, Elena Carmen (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2018)
This contribution studies the assigned role to the defense of the traditional family””based on indissoluble, heterosexual, monogamous, and patriarchal marriage””in a catholic counterrevolutionary lay strategy during the 60’s. This group was organized around the journal Crusade as well around the influence of the Brazilian thinker Plinio Corrêa de Oliveira. Under his patronage this group founded the group Argentine Society in Defense of Tradition, Family, and Property (TFP). In this context, the study reviews the role of Crusade inside the catholic movement, its disseminating modes in order to highlight ambiguities of the so-called modernization process